TRADITIONS AND LEGAL FOUNDATIONS OF STATE ADMINISTRATION IN THE SELJUKS (American Journal of Interdisciplinary Research and Development, 2023)
In this article, the Seljuks state administration, history and duties of management officials are highlighted.